Implementasi Kebijakan Pengendalian Penggunaan BBM Bersubsidi untuk Kendaraan Dinas di Kota Semarang - Saffanah, Afina Putri; Kismartini, Kismartini; Rostyaningsih, Dewi (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Fuel Oil Control Policy refer to Regulation of the Minister of Energy and Mineral Resources No. 1 2013 regarding control of the use of a particular fuel oil. The fuel oil subsidy control program aims to stabilize the fuel oil consumption, fuel oil subsidies are mainly so that in the future can still be consumed. As we know that all our needs there is no escape from a fuel oil, whether it be of processing or use. So with the fuel oil control is expected to continue to meet the needs now and in the future. The process of implementation of the policy of fuel oil control in achieving the goal of factor supporting and inhibitors factors. Based on the theory of George Edward III, factors that support and hinder form of Resources, Bureaucratic Structure, Communication, and Disposition.The factors supporting the implementation of the fuel oil control include:human resources of the actors implementing sufficient resources to FUEL the build-up would be adequate, there is a consistency of information from the Government, the SOP has been understood by the executor, the coordination is going well, behavior implementer policy is according to the role of each inÂ existing regulations. And inhibiting factors are not sufficient budget resources needs of the users of official vehicles, the lack of readiness of the user service vehicles in implementing existing regulations, the sanctions have not been applied strictly.Â